SOCIAL INFRASTRUCTURE OF ACTUARIAL PENSION PAYMENTS AS A WAY OF OVERCOMING A BUDGET DEFICIT - Oleg A. Donichev; Anna V. Novikova (Статистика и экономика)
The article is devoted to the problem of overcoming the lack of funding the revenue side of the Pension Fund of the Russian Federation. The ways of further development of the funded component of future pension payments are proposed in the article. The need to form in regions the adequate social infrastructure which could enable to develop the funded pension systems is specified in the article.